“House Fathers” and “People of the Fields” in Art and Folk Literature Since the Reformation - Scheuerman, Richard D.; Ellis, Arthur (International Dialogues on Education Journal, 2017)
Themes related to humanity’s relationship to nature as technological change led to the Industrial Revolution are evident in early modern German and Austrian art and literature. Authors of popular Hausväterliteratur (house fathers’ literature) associated with the Protestant Reformation advocated the rudiments of agricultural “improvement” through division and specialization of agrarian labor, plant selection, crop rotation, and other changes that upper class landowners adopted for their own economic benefit. By the nineteenth century, authors of Volksliteratur and Dorfgeschichten(village stories) composed novels and short stories celebrating aspects of rural culture and land stewardship as both values were increasingly threatened by modernity. In his writings on Die Gute Gesellschaft (The Good Society), Peter Rosegger cautioned against preoccupation with technical progress that was contributing to rural depopulation and erosion of the sustaining Volksgeist (folk spririt) of locale, community, and obligation.